Dominant Indicator of Creative Thinking: The Case of Geography Learning Outcomes - Faisal Arif Setiawan; Akhmad Munaya Rahman; Sarifah Triana; Mustika Arif Jayanti (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
Creative thinking were considered skills usually based on natural talent. It means that only those who were talented could become creative people. The reality, the students can create new ideas quickly and diversely. This article aimed to determine the dominant indicators of creative thinking between fluency, flexibility, originality, and elaboration. The subjects were 29 high school students in one class, and the learning process aimed to increase creativity. Measure creativity by using subjective questions, such as as as many as five questions. The learning outcome score was the final grade of the semester. Data analysis used multiple linear regression. The results showed that the flexibility indicator has a β value most distant from zero (0) (β = 4,030). The flexibility indicator was the most dominant and has the most significant influence compared to other indicators. Flexibility helped students deal with these obstacles by finding alternatives or changing strategies. Identifying major creative thinking indicators was a foundation for building unique evaluation methodologies. The contribution for methodologies can better assess students' creative ability and grasp of geographical ideas, resulting in a more comprehensive evaluation of student performance.